HIV Seroconversion in blood donors from the coordinating blood bank in the State of Pará - Costa,Andrea Silvestre Lobão (2011)
BACKGROUND: Transfusion of Human immunodeficiency virus (HIV) infected blood is probably the most effective means of transmission of this disease. Despite intense efforts and investment to ensure safety, transmission of HIV still remains a real possibility in the transfusion service due to the fact that routine laboratory tests in most Brazilian government blood banks rely on the detection of antibodies. This leaves an immunological window period of from 16 to 22 days, which could be minimized to approximately 9 to 11 days if nucleic acid amplification tests were employed in screening. OBJECTIVE: To analyze the profile of blood donors who seroconverted to HIV positive from 2008 to 2010 in the coordinating blood bank of the State of Pará in respect to gender, age, marital status and educational level. METHODS: HIV seroconversion cases of blood donors who donated on more than one occasion at the coordinating blood bank of the State of Pará were investigated. Records from 2008 and 2010 were analyzed in respect to gender, marital status, schooling and age. RESULTS: Among the 157,432 donations in this period, 45 HIV seroconversions were confirmed. Of these, 95.56% were men, of which 86.67% were single, 53.33% had completed high school and 40% were between 23 and 29 years old. CONCLUSIONS: In order to improve the quality of blood and reduce the residual risk of HIV transmission in blood banks, it is necessary to know the profiles of donors who most frequently seroconvert and use nucleic acid amplification tests as routine screening.